Pharmacodynamics of benserazide assessed by its effects on endogenous and exogenous levodopa pharmacokinetics* - Dingemanse, Jasper (1997)
Aims The objectives of the study were to investigate the pharmacodynamics of the peripheral decarboxylase inhibitor benserazide during multiple-dose regimens. Methods Two groups of eight healthy male subjects were consecutively treated for periods of 14 days with benserazide 5, 25, 100 mg three times daily and 12.5, 50, 200 mg three times daily, respectively. Plasma levels of levodopa, 3-O-methyldopa (3-OMD) and 3,4-dihydroxyphenylacetic acid (DOPAC) were determined before benserazide treatment and during all benserazide dosing regimens, as existing endogenously and after administration of 250 mg levodopa. Results Endogenous concentrations of levodopa and 3-OMD increased dose-dependently (from 8 up to 52 μg l(−1) and from 0.02 up to 0.50 mg l(−1), respectively, at doses of 200 mg) with ascending doses of benserazide whereas DOPAC levels remained unchanged. There were no indications of a plateau in the effects of benserazide on the plasma levels of the analytes. The area under the concentration-time curve (AUC) of exogenously administered levodopa increased from 1.2 in the control group to 5.9 mg l(−1) h at benserazide doses of 100–200 mg three times daily. Benserazide caused a dose-dependent increase in the AUC of 3-OMD from 7.4 to 106 mg l(−1) h at doses of 200 mg. Formation of DOPAC was dose-dependently suppressed, with benserazide 5 mg three times daily already halving its AUC. Conclusions The benserazide-dose response data obtained suggest that even at very high doses extracerebral decarboxylase is not yet completely inhibited.